PENGARUH IPM DAN UMK TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI JAWA TENGAH - Solicha, Firda Armaatus; Agustin, Indah Dwi; Efend, Silvie Putri Wahyu; Arisetyawan, Kukuh; Nilasari, Aprillia (Universitas Negeri Surabaya, 2024)
The labour force participation rate is a crucial indicator of a region's economic dynamics, since an imbalance between labour force growth and job creation can result in elevated unemployment and hinder regional development. The government attempts to increase labor force participation by improving the quality of human resources and setting the minimum wage. This study uses BPS data and panel data regression analysis to determine the effect of the Human Development Index (HDI) and MSE (District/City Minimum Wage) on the labor force participation rate in Central Java. The findings of this study show that MSEs have no significant impact on labor force participation in Central Java Province, but HDI has a significant impact.